Pelaksanaan Program Strategi Pengembangan UMKM pada Bagian Perekonomian Sekretariat Daerah Kota Palembang - Andaryani, Sutinah; Irrayana, Irrayana (Jurnal Publisitas, 2022)
This research was to find out the Implementation of the Micro, Small and Medium Enterprises (MSME) Development Strategy Program in the Economic Section of Palembang Regional Secretariat. This research was a qualitative research using a descriptive approach. Collecting data was taking by in-depth interviews, observation and documentation. The data were analyzed by qualitative data analysis techniques. Based on the results of the study, there were three indicators, (1) the making of Integrated Information. The development of integrated information could make easier for public to communicate with the government, such as related to licensing process and the development of MSMEs through programs issued by government. The website provided as an integrated information target was https://hallo.palembang.go.id and https://lapor.go.id. (2) The establishment of a MSME Consulting and Development Center. The Economic Section of Palembang Regional Secretariat is a local government agency that provided a consultation center in collaboration with the Cooperatives and MSMEs Service Palembang, but in its implementation there were not many visitors came to the place. In addition to consultation center, the strategy conducted by obtaining aspirations from the community related to business development in Palembang was establishing associations through MUSRENBANG from village to sub-district levels which were driven by Regional Planning Agency Palembang. Moreover, the Economic Section of Regional Secretariat Palembang in collaboration with the Cooperatives and MSME Service could also choose priority activities and conducted industrial and trade development planning that led to the priority of real community needs and in accordance with the potential conditions of the districts. (3) The Joint Marketing System, in this case the Economy Section of Palembang Regional Secretariat worked with the Cooperatives and MSME Service of Palembang had been able to implement a strategy to create a joint marketing system for SMEs in Palembang, one of which was by creating a Forum with the Regional Crafts Council Palembang (DEKRANASDA) which existed in Palembang. This forum accommodated all MSME products. In addition to the Forum, the Regions that provided joint marketing through Local and Regional Level Exhibitions were held once a year, they were the anniversary of Palembang and the anniversary of the Province of South Sumatra.